THE USE OF DIRECT STRATEGIES IN READING COMPREHENSION : (A Descriptive Study at Senior High School Al-Falah Abu Lam U Aceh Besar) - Rusmiati; Kamalina (Getsempena English Education Journal, 2016)
The purpose of this research is to know the direct strategies used by students in reading comprehension at SMA Islam Al-Falah Abu Lam U. The subject of this research is the first grade students of XI 1 at SMA Islam Al-Falah Abu Lam U. Descriptive qualitative method is used to describe the strategies used by students in reading comprehension. The data of this research were obtained by using observation, questionnaire and interview. They are analyzed by using a descriptive explanation. The result show that the students at SMA Islam Al-Falah Abu Lam U used many cognitive strategies in reading comprehension, such as word by word translation, meaningful translation, use dictionary, underlying of keyword and many others. The use of these strategies is to help students in reading comprehension, namely to comprehend the text easily and rapidly. The cognitive strategies that frequently used by students were; using dictionary (resourcing), translated word by word (repetition), reading the title and imagines what the text might be about (summarizing), and reading with comprehend every paragraph to understand whole text (deduction).